1982
DOI: 10.1017/s003329170005563x
|View full text |Cite
|
Sign up to set email alerts
|

Non-MAOI antidepressant drugs and cognitive functions: a review

Abstract: SYNOPSISLittle is known about the effects of non-MAOI antidepressants on cognitive functions, despite their wide application to ambulant patients. Evidence from studies involving healthy volunteers suggests that differences exist between drugs, with imipramine, amitriptyline and mianserin being associated with the most marked detrimental effects. However, these findings have generally not been supported by the few studies using clinical populations, for which improvements in cognitive functions are often recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 36 publications
0
13
0
1
Order By: Relevance
“…The results clearly show that idazoxan does not significantly impair performance of any task nor increase negative effect. This gives it distinct advantages over conventional antidepressants (such as amitryptyline) which often have sedative effects or produce attentional and mnemonic decrements (see Thompson and Trimble, 1982;Curran, 1992). Indeed, idazoxan improved one aspect of selective attention, the place repetition effect.…”
Section: Discussionmentioning
confidence: 99%
“…The results clearly show that idazoxan does not significantly impair performance of any task nor increase negative effect. This gives it distinct advantages over conventional antidepressants (such as amitryptyline) which often have sedative effects or produce attentional and mnemonic decrements (see Thompson and Trimble, 1982;Curran, 1992). Indeed, idazoxan improved one aspect of selective attention, the place repetition effect.…”
Section: Discussionmentioning
confidence: 99%
“…The number of investigations exploring the effects of antidepressant drugs on memory and other cognitive functions had increased since a previous review (Thompson and Trimble, 1982). Conflicting findings on the same drug still exist, and are attributable to significant methodological differences between the studies.…”
Section: Discussionmentioning
confidence: 99%
“…In depressive patients and in normals (Deptula and Pomara, 1990; Thompson, 1991; Thompson and Trimble, 1982) the effects of tricyclic antidepressants on psychomotor and cognitive functions are inconsistent. Indeed, studies with imipramine in depressed patients have shown (a) performance impairment (Calev et al, 1989;Jones et al, 1986;Legg and Stiff, 1976;Wittenborn et al, 1976), (b) performance improvement (Amin, Khan and Lehmann, 1980;Glass, Uhlenhuth and Weinribb, 1978;Sternberg and Jarvik, 1976) or (c) no effect at all (Henry, Weingartner and Murphy, 1973;Raskin, Friedman and DiMascio, 1983;Wittenborn et al, 1962).…”
Section: Introductionmentioning
confidence: 99%